The Sacrifice of Knowledge: Vain Debates in the Social Scientific Study of Religion - Kramp, Joseph M. (Journal of religion and health, 2013)
Since its inception, the social scientific study of religion has been a battleground for scholars advocating for the advantages of one sort of methodology over against the other. I argue that these debates have more to do with the personalities of the researchers rather than any kind of justifiable proof that one method is better than another. I argue that the process by which scholars quarrel over methods is a sign of stagnation or regression in the academy; I draw broad implications for the health of the discipline of religious studies.